2017
DOI: 10.22354/in.v21i1.646
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia y factores relacionados con la infección por Clostridium difficile en un centro hospitalario de alta complejidad en Cali (Colombia)

Abstract: Prevalencia y factores relacionados con la infección por Clostridium difficile en un centro hospitalario de alta complejidad en Cali (Colombia) ResumenObjetivos: Estimar la prevalencia y los factores relacionados con la infección por Clostridium difficile en un hospital de alta complejidad en Cali (Colombia). Métodos: Se realizó un estudio de casos y controles en pacientes que consultaron por diarrea o la desarrollaron durante la hospitalización y que tuvieron un resultado positivo en la prueba de PCR para Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Our CART showed that if a patient had a history of antibiotic use, the probability of a positive PCR was 45.7%. Previous studies in this matter showed almost all antibiotics can increase vulnerability to CDI, but cephalosporins, fluoroquinolones, clindamycin, and certain penicillins (e.g., amoxicillin/clavulanic acid) increase risk to the greatest extent (8,14,15). Above supports the results of this study regarding consider this exposure in the decision to perform a PCR.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our CART showed that if a patient had a history of antibiotic use, the probability of a positive PCR was 45.7%. Previous studies in this matter showed almost all antibiotics can increase vulnerability to CDI, but cephalosporins, fluoroquinolones, clindamycin, and certain penicillins (e.g., amoxicillin/clavulanic acid) increase risk to the greatest extent (8,14,15). Above supports the results of this study regarding consider this exposure in the decision to perform a PCR.…”
Section: Discussionsupporting
confidence: 86%
“…In low and middle-income countries, there is a lack of evidence-based diagnostic algorithms for early CDI diagnosis using a PCR test. In 2011, a study showed that the prevalence of in-hospital C. difficile was 10 per 10.000 inpatients in Cali, indicating a high prevalence of this infection and the need to identified better strategies for the control of C. difficile (14). Our study shows a straightforward algorithm that includes clinically relevant variables and may help clinicians in the diagnostic process of patients with suspected CDI.…”
Section: Discussionmentioning
confidence: 87%